The Mediation of Emotions in Sport Events: A Case Study in Badminton. (May 2021) - Cabello-Manrique, David; Nuviala, Román; Pappous, Athanasios (Sakis); Puga-González, Esther; Nuviala, Alberto
This study examines the relationships between functional quality, outcome quality, satisfaction, and future intentions, influenced by emotions, of spectators who attended the 2018 European Badminton Championships. The population studied was 686 spectators. The mean age was 36.08 ± 14.15 years, 39.1% were females, and 66.1% were local resident spectators. The results allow to affirm that functional quality and outcome quality have an impact on satisfaction, either directly or indirectly through emotions. In the same way, it has been possible to observe the relationship between satisfaction and future intentions of the spectators. These results help understand the factors that predict the loyalty of spectators of sports events of badminton.